Acts of the Constitutional Court of Ukraine as an effective mechanism for the protection of human rights and freedoms in administrative proceedings - Tsymbalistyi, Taras (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article examines the issues of the relationship between constitutional and administrative justice, the legal nature of the acts of the Constitutional Court of Ukraine. The forms of protection by the body of constitutional justice of the rights and freedoms of man and citizen, in particular in the field of administrative legal proceedings, are analyzed.